Exploring virtual coach education in USA Lacrosse - Langdon, J.; Van Arkel, J.; Greene, K. (International Sport Coaching Journal, 2023)
In 2020, USA Lacrosse moved all coach training workshops to a virtual format in response to the COVID-19 pandemic. Knowing that in-person coach training has been heavily studied regarding the motivation of the coaches who participate, the shift to virtual delivery of coach education prompted the researchers to examine how the workshops themselves supported the basic needs, motivation, and engagement of coach learners. Aligned with self-determination theory`s conception of motivation and the three basic needs of autonomy, competence, and relatedness, the researchers drew upon observation and survey data that were collected to determine the success of the virtual training. Using this information, the researchers found that the coach trainers used a variety of need-supportive behaviors and very few need-thwarting behaviors. Surveys revealed that the coaches displayed high levels of autonomous motivation, low levels of controlled motivation, and favorable engagement. These results are discussed in conjunction with the literature that is focused on in-person training programs as well as best practices in technology-enhanced learning to provide input into how virtual programming may be of benefit to coach learners and how coach trainers can best support coaches` needs in a virtual environment.